2013
DOI: 10.1038/ki.2012.477
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin K and therapeutic warfarin alter the susceptibility to vascular calcification in experimental chronic kidney disease

Abstract: The leading cause of death in patients with chronic kidney disease (CKD) is cardiovascular disease, with vascular calcification being a key modifier of disease progression. A local regulator of vascular calcification is vitamin K. This γ-glutamyl carboxylase substrate is an essential cofactor in the activation of several extracellular matrix proteins that inhibit calcification. Warfarin, a common therapy in dialysis patients, inhibits the recycling of vitamin K and thereby decreases the inhibitory activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 33 publications
6
126
1
Order By: Relevance
“…More interestingly, hyperparathyroidism was an independent predictor for kidney progression, which had not been fully shown previously (30), whereas low vitamin D levels were associated to all-cause mortality and ESRD after adjusting for age and eGFR, respectively. Lastly, we would like to draw attention to the independent association observed between the use of oral anticoagulants and VC, which has been previously reported (33)(34)(35). Although this association does not imply causation, it should be evaluated in future clinical trials designed to test anticoagulation strategies in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, hyperparathyroidism was an independent predictor for kidney progression, which had not been fully shown previously (30), whereas low vitamin D levels were associated to all-cause mortality and ESRD after adjusting for age and eGFR, respectively. Lastly, we would like to draw attention to the independent association observed between the use of oral anticoagulants and VC, which has been previously reported (33)(34)(35). Although this association does not imply causation, it should be evaluated in future clinical trials designed to test anticoagulation strategies in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K antagonists, such as warfarin, are used commonly in CKD patients and interfere with the generation of active MGP (88). Adenine-induced CKD mice treated with therapeutic doses of warfarin develop significant vascular calcification, and warfarin use is associated with vascular calcification in the hemodialysis population (48,69). Circulating levels of dephosphorylated uncarboxylated (inactive) MGP have been found to increase with worsening stages of CKD, and these elevated levels are associated with the severity of aortic calcification.…”
Section: Risk Factors For Vascular Calcification In Ckdmentioning
confidence: 99%
“…McCabe et al (23) similarly reported increased vascular calcification in rats with CKD on warfarin, which was also blunted by vitamin K. In a retrospective study of 108 haemodialysis (HD) patients, an association was found between duration of warfarin exposure and degree of aortic valve calcification after adjustment for dialysis vintage, calcium and calcitriol intake (24). Furthermore, a recent Japanese study found an 11-fold risk in HD patients on warfarin for calciphylaxis (uraemic calcific arteriolopathy), an uncommon complication of ESKD characterised by skin ulceration and necrosis with small vessel medial calcification and intimal proliferation (25).…”
Section: Warfarin In Dialysis Patientsmentioning
confidence: 99%